Analyzing the Impact of Natural Resource Rents, Green Finance and Digital Finance on Environmental Quality: Evidence from Developing Countries - Permana, Dudi; Salim, Ansa Savad; Ramli, Yanto; Shamansurova, Zilola (International Journal of Energy Economics and Policy, 2024)
Most of the developing economies face the issue of environmental degradation despite having tremendous growth in previous decades. Therefore, these countries are not able to preserve their development level if they do not achieve their targets of environmental sustainability. In this view, this study aims to analyze the effect of green finance, digital finance and natural resources on carbon dioxide (CO2) emissions for a panel of 23 developing countries over 2010 to 2020 period. The study has applied Driscoll-Kraay Standard Error estimation technique to conduct the empirical estimation. The outcomes of the study identify that natural resources and digital finance reduce, whereas green finance increase the level of CO2 emissions. The findings of causality test indicate that green finance, digital finance and natural resources do not granger cause the CO2 emissions. Thus, natural resources and digital finance have significant contribution to improve the environmental quality. Based on the findings, the study recommends relevant policies for the effective utilization of natural resources and promoting digital finance to achieve the targets of environmental sustainability in developing countries.